Complete Response After Pre-Operative Transcatheter Arterial Chemoembolization for Unresectable Primary Hepatic Neuroendocrine Tumour: A Case Report and Literature Review - Xinyuan Zhang; Huiru Yang; Yujing Xin; Yi Yang; Haizhen Lu; Xiang Zhou (Frontiers in Oncology, 2022)
BackgroundPrimary hepatic neuroendocrine tumours (PHNET) are extremely rare. Currently, no evidence-based guidelines are available for PHNET treatment, especially for unresectable tumours.Case PresentationWe present the case of a 43-year-old man who was admitted to our hospital with complaints of backache for more than 1 month. The imaging examination showed a 5.5×5.3 cm lesion in the liver and no extrahepatic lesions, which was confirmed as a grade 2 PHNET by the pathological results and exclusion of non-hepatic origins. A multidisciplinary team (MDT) consultation revealed that the lesion was an unresectable primary hepatic neuroendocrine tumour (uPHNET) but could be potentially treated by conversion surgery. The patient was initially administered four cycles of chemotherapy with temozolomide, 5-fluorouracil, and ondansetron, and was evaluated as stable disease (SD) according to the Response Evaluation Criteria in Solid Tumours version 1.1 (RECIST 1.1). Because of the limited clinical benefit of chemotherapy, the patient subsequently underwent transcatheter arterial chemoembolisation (TACE) treatment, which reduced the tumour size and converted uPHNET to resectable tumours. A complete response (CR) was achieved after surgery, and the patient has been disease-free.ConclusionsThis case was reported by a patient with uPHNET who benefited from the pre-operative TACE, providing a potentially effective management strategy for refractory tumours.